(4x+1)^2 - (1-3x)(1+3x)=(5x+2)^2
(16x^2+8x+1) - (1 - 9x^2) = 25x^2+20x+4
16x^2+8x+1 - 1+9x^2 = 25x^2+20x+4
25x^2 + 8x = 25x^2+20x+4
25x^2 - 25x^2 - 20x + 8x = 4
-12x = 4
x = -4/12
x = -1/3
ответ: -1/3
1)
30% числа k = 0,3a
35% числа p = 0,35p
0,3k > 0,35p на 20
Первое уравнение:
0,3k - 0,35p = 20
2)
20% числа k = 0,2а
30% числа p = 0,3р
0,3р > 0,2k на 8
Второе уравнение:
0,2k + 8 = 0,3p
3)
Решаем систему.
{0,3k-0,35р = 20
{0,2k - 0,3р = - 8
Первое умножим на 2, а второе умножим на (-3)
{0,6k-0,7р = 40
{-0,6k+0,9р = 24
Сложим
0,6k-0,7р -0,6k+0,9р = 40+24
0,2р = 64
р = 64 : 0,2
р = 320
В первое уравнение 0,3k - 0,35p = 20 подставим р = 320.
0,3k - 0,35·320 = 20
0,3k - 112 = 20
0,3k = 112 + 20
0,3k = 132
k = 132 : 0,3
k = 440
ответ: k = 440;
р = 320.
(4х+1)²-(1-3х)(1+3х)=(5х+2)²
16х²+8х+1-(1-9х²)=25х²+20х+4
16х²+8х+1-1+9х²=25х²+20х+4
25х²+8х-25х²-20х-4=0
-12х-4=0
-12х=4
х=-4/12
х=-1/3